Exploring Official Academic Integrity Data - Lam, Anita; McManus, Angelica (Canadian Perspectives on Academic Integrity, 2023)
As academic honesty policies are being revised at Canadian universities, in order to balance the maintenance of rigorous standards of academic conduct with principles of anti-racism and equity, diversity and inclusion, data on academic honesty breaches become an important source of information for policymaking and improvement of existing practices. Rather than examine the usual kinds of self-report and student survey data found in the scholarship on academic integrity, this presentation explores what conclusions can be drawn from so-called official data on academic honesty breaches in the largest liberal arts faculty in Canada. Collected over two years during the height of the COVID-19 pandemic in Canada, this faculty-level data highlights how academic dishonesty incidents, although counted as instances of individual student misconduct, point to larger systemic issues in teaching and learning in higher education. When performed under emergency, pandemic conditions, online teaching and learning had the effect of exacerbating poor assessment design and learner disengagement at a time when predatory third parties were offering online contract cheating services, especially to racialized students. While present data reporting relies on making a distinction between domestic and international students, such a categorical difference obscures the ways in which racialized students, irrespective of VISA status, are disproportionately caught in the web of academic honesty processes. If data-driven decision-making will help shape the future of academic integrity policies and practices, then it is imperative that we recognize the limitations embedded in the official data that we currently collect.